TAX AVOIDANCE, RELATED PARTY TRANSACTIONS, CORPORATE GOVERNANCE AND THE CORPORATE CASH DIVIDEND POLICY - Dewi Kartika Sari; Sidharta Utama; Hilda Rossieta (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
This study aims to investigate the relationship between tax avoidance, related party transactions and the corporate dividend policy. Furthermore, this study will also investigate the moderating effects of the implementation of Corporate Governance (CG) on the relationship between tax avoidance, Related Party Transactions (RPT) and corporate dividend policies. Our sample covers companies listed on the Indonesian Stock Exchange during 2011-2014. The results provide moderate support for the proposed hypotheses. First, the greater tax avoidance that a company makes will increase the size of the firm's RPT. Second, the higher that the company's RPT is, this will lower the company's cash dividend payout rate. Third, the greater the tax avoidance is, the lower the company's cash dividend payout rate will be, which is done through a related party transaction.Fourth, the impact of the implementation of strong CG will weaken the positive relationship between corporate tax avoidance and the company’s RPT size, strengthen the negative relationship between the RPT’s size and the cash dividend payout policy of the firm, and strengthen the negative relationship between the company’s tax avoidance and the company's cash dividend payout policy which is mediated by the company’s RPT. This study makes three contributions. First, this study shows an indirect relationship between tax avoidance and cash dividend payments, mediated by RPT. Second, this study tries to examine the effect of CG’s moderation on the relationship between tax avoidance and RPT, as well as the effect of CG’s moderation on the relationship between tax avoidance and cash dividend payments, mediated by RPT. Third, this study developed RPT measurements by looking at the RPT’s components more specifically (looking at components of transactions outside of the main business of the company - the